The repercussions of the Corona virus pandemic on the symptoms of obsessive-compulsive disorder from the point of view of Saudi society - Alamin, Rehab Mohamed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the repercussions of the emerging corona pandemic on the symptoms of obsessive-compulsive disorder from the point of view of the Saudi society, where the researcher, and applied the study sample, which consisted of 269 randomly selected individuals, and by descriptive analytical approach, and the results concluded that the coronavirus pandemic exacerbated the symptoms of obsessive-compulsive disorder among people with obsessive-compulsive disorder, as (42%) of those who had OCD or were diagnosed with OCD stressed the need for OCD sufferers to visit the hospital for treatment during the pandemic period. The majority of the study subjects who were not previously diagnosed with obsessive-compulsive disorder said that they rarely have the idea of repeating washing and sterilizing things with a percentage of (41.6%), while the percentage (36.1%) of those who were not previously diagnosed with obsessive-compulsive disorder have always an urgent desire to repeat washing and sterilizing things. And this may be an indication of the emergence of symptoms of disorder in the future for some members of Saudi society, and the researcher presented a recommendations and suggestions, including the necessity of spreading awareness among members of society and educating them about obsessive-compulsive disorder in terms of causes and symptoms. She called for conducting scientific studies and research dealing with obsessive-compulsive disorder during the Corona pandemic and after the pandemic. For example, obsessive-compulsive disorder patients.
Keywords: Obsessive Compulsive Disorder; OCD; Covid-19; Coronavirus